Melody® pulmonary valve bacterial endocarditis: Experience in four pediatric patients and a review of the literature. Issue 2 (31st January 2014) - Villafañe, Juan; Baker, George Hamilton; Austin, Erle H.; Miller, Stephen; Peng, Lynn; Beekman, Robert
<x xml:space="preserve">Abstract</x> Objectives The objectives of this manuscript are two‐fold: (a) to describe the clinical characteristics and management of four pediatric patients with bacterial endocarditis (BE) after Melody® pulmonary valve implantation (MPVI); and (b) to review the literature regarding Melody® pulmonary valve endocarditis. Background There are several reports of BE following MPVI. The clinical course, BE management and outcome remain poorly defined. Methods This is a multi‐center report of four pediatric patients with repaired tetralogy of Fallot (TOF) and BE after MPVI. Clinical presentation, echocardiogram findings, infecting organism, BE management, and follow‐up assessment are described. We review available literature on Melody® pulmonary valve endocarditis and discuss the prognosis and challenges in the management of these patients. Results Of our four BE patients, two had documented vegetations and three showed worsening pulmonary stenosis. All patients remain asymptomatic after medical treatment (4) and surgical prosthesis replacement (3) at follow‐up of 17 to 40 months. Analysis of published data shows that over half of patients undergo bioprosthesis explantation and that there is a 13% overall mortality. The most common BE pathogens are the Staphylococcus and Streptococcus species. Conclusions Our case series of four pediatric patients with repaired TOF confirms a risk for BE after MPVI. A high index of suspicion for BE should be observed after MPVI. All patients should be advised to follow lifelong BE prophylaxis after MPVI. In case of BE, surgery should be considered for valve dysfunction or no clinical improvement in spite of medical treatment. © 2014 Wiley Periodicals, Inc.